Enhancing Student Autonomy and Moral Awareness through Regulatory Compliance-Based Reflective Learning - Zalil, Muhammad Abdul; Aspandi, Ade; Muhammad Azhar Muttaqin; Mima, Nur Luthfiyani Fajrin (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to analyze the implementation and explore the impact of regulatory compliance-based reflective learning at Bina Insan Mulia Islamic Boarding School as a strategy to enhance students’ autonomy and moral awareness. The research focuses on how adherence to educational regulations serves as an ethical framework for improving learning quality. A Classroom Action Research (CAR) design employing a descriptive qualitative approach was applied. Data were collected through classroom observations, teacher reflections, and student interviews over two action cycles. The analysis revealed that regulatory-based reflective learning not only enhanced students’ motivation and responsibility but also fostered self-autonomy and moral awareness. Overall, the model demonstrates a synergy between pedagogical innovation and legal compliance, cultivating an ethical and independent learning culture aligned with national education principles.